2020
DOI: 10.3892/mmr.2020.11032
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of antisense long non‑coding RNA ZNF710‑AS1‑202 promotes cell proliferation and inhibits apoptosis of clear cell renal cell carcinoma via regulation of ZNF710 expression

Abstract: antisense long non-coding rnas (aS lncrnas) have been increasingly recognized as important regulators of gene expression and have been found to play crucial roles in the development and progression of tumors. The present study explored the roles of aS lncrna ZnF710-aS1-202 in clear cell renal cell carcinoma (ccrcc). The expression levels of ZnF710-aS1-202 were detected in 46 human ccrcc tissues and 34 healthy adjacent renal tissues. The associations between the levels of ZnF710-aS1-202 expression and the clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In a recent study, Li and colleagues found that ZNF710-AS1-202 played a role in enhancing cell growth and suppressing cell death in clear cell renal cell carcinoma through the reverse regulation of ZNF710[ 30 ]. Nevertheless, there is no existing report on the regulatory impact of ZNF710-AS1-201 on tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Li and colleagues found that ZNF710-AS1-202 played a role in enhancing cell growth and suppressing cell death in clear cell renal cell carcinoma through the reverse regulation of ZNF710[ 30 ]. Nevertheless, there is no existing report on the regulatory impact of ZNF710-AS1-201 on tumors.…”
Section: Discussionmentioning
confidence: 99%
“…RP11-617F23.1 was also known as ZNF710-AS1-201 according to Ensembl database. Only one report concerning ZNF710-AS1-201, which demonstrated that the overexpression of ZNF710-AS1-201 was correlated with poor prognosis for patients with clear cell renal cell carcinoma [ 35 ]. This conclusion was consistent with our verification result.…”
Section: Discussionmentioning
confidence: 99%
“…ZNF710-AS1-202: The ZNF710-AS1-202 is a newly-found lncRNA, which was first unveiled to be a tumor suppressor in RCC and was significantly declined in RCC tissues 93 For example, the serum gradually increased during hepatocarcinogenesis (GIHCG) was significantly increased in RCC patients and can distinguish RCC patients from healthy controls with an AUC of 0.920 in the testing set 95 . Similarly, another study indicated that serum C-X-C motif chemokine ligand 2 (CXCL2) level was markedly higher than that in healthy subjects.…”
Section: Linc01939mentioning
confidence: 99%